Back to Contract? - William C. Jones (Washington University Law Quarterly, 1964)
The idea of contract no longer has the prestige that it once did. No one would write today, as Maine did, that “the society of our day is mainly distinguished from that of preceding generations by the largeness of the sphere which is occupied in it by Contract.” The concept of two private individuals bargaining and forming an agreement that will govern their relationship is foreign to the world of the Collective Bargaining Agreement, government or other form contracts, acreage limitations, the Securities and Exchange Commission, Telstar and all the rest of it. Despite this, in areas in which individuals do still deal with each other on an individual basis, there is a very strong tendency to have the relationship governed by contract, by the agreement the parties have made, and not by any externally imposed norms. This is notably the case with marriage, which most courts today in fact regard as a contractual relationship, which can be terminated when the parties wish, and in accordance with the terms that they have agreed on, although the legal theory is, of course, quite different. The extraordinary thing is that the one area of the law which one would expect to be entirely contractual—the sale of goods—appears to be nothing of the sort. Such concepts as “warranties” of quality, “title,” and “passage of property” are all too clearly derived from the law of property, not contract.
Keywords: Contracts; Sales